Author Correction: Tropical forests as drivers of lake carbon burial - Amora-Nogueira, Leonardo; Sanders, Christian J.; Enrich-Prast, Alex; Sanders, Luciana Silva Monteiro; Abuchacra, Rodrigo Coutinho; Moreira-Turcq, Patricia F.; Cordeiro, Renato Campello; Gauci, Vincent; Moreira, Luciane Silva; Machado-Silva, Fausto; Libonati, Renata; Fonseca, Thairiny; et al. (Nature communications, 2023)
which incorrectly read. 'We find that humid tropical forest lake sediments are a disproportionately important global OC sink of ~80 Tg C yr -1 with implications for climate change.'The correct version replaces this sentence with 'We find that humid tropical forest lake sediments are a disproportionately important global OC sink of ~7.4 Tg C yr -1 with implications for climate change.'The original version of this Article contained an error in the 'Tropical drivers of OC accumulation in lakes' section, which incorrectly read.'Applying our recent OC burial rates to global lake area 13 resulted in an estimated global sink of 79 Tg C yr -1 , which is equivalent to ~27% of estimated global carbon dioxide (CO 2 ) emissions from lake waters to the atmosphere (i.e., 292 Tg C yr -1 ) 20 'The correct version replaces this sentence with 'Applying our recent OC burial rates to global lake area 13 resulted in an estimated global sink of 80 Tg C yr -1 , which is equivalent to ~27% of estimated global carbon dioxide (CO 2 ) emissions from lake waters to the atmosphere (i.e., 292 Tg C yr -1 ) 20 'This has been corrected in both the PDF and HTML versions of the article.